1997
DOI: 10.1046/j.1365-2958.1997.5991975.x
|View full text |Cite
|
Sign up to set email alerts
|

Instability of artificially circularized chromosomes of Streptomyces lividans

Abstract: SummaryThe chromosomes of Streptomyces species are linear molecules, containing long terminal inverted repeats and covalently bound terminal proteins. These chromosomes undergo spontaneous deletions of the terminal sequences at high frequencies and become circularized in several cases examined. Artificial circularization of the Streptomyces lividans chromosome was also achieved by targeted recombination in vivo, in which the terminal inverted repeats of the chromosome were connected by a kanamycin resistance g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…The apparent association of deletion and amplification cycles with the end regions of the linear chromosome, although probably not in an obligate way, has recently given the topic a new impetus (e.g. Lin & Chen, 1997 ;Volff & Altenbuchner, 1998).…”
Section: The In Vitro Yearsmentioning
confidence: 99%
“…The apparent association of deletion and amplification cycles with the end regions of the linear chromosome, although probably not in an obligate way, has recently given the topic a new impetus (e.g. Lin & Chen, 1997 ;Volff & Altenbuchner, 1998).…”
Section: The In Vitro Yearsmentioning
confidence: 99%
“…While certain strains of S. lividans have linear chromosomes, others have undergone DNA rearrangements that result in chromosome circularization and the loss of telomeres (Lin and Chen 1997;Volff et al 1997;Volff and Altenbuchner 2000). Like the telomeres of S. rochei linear plasmids, the 5Ј ends of S. lividans linear chromosomal DNA are protected by covalently attached protein (Lin et al 1993).…”
Section: The Terminal Protein Gene Of Streptomyces Lividans Zx7mentioning
confidence: 99%
“…However, during these experiments, we observed rare spc r tsr s survivors (frequency ∼ 10 −3 versus our normal gene replacement frequency of 10 ); examination of several of these survivors by Southern blot analysis confirmed disruption of the tpgL gene, as shown in Figure 4, B and C, for BKKO5. When telomeres are deleted from Streptomyces linear replicons, the internal replication origin allows their propagation as circular DNA molecules (Shiffman and Cohen 1992;Lin et al 1993;Chang and Cohen 1994;Chang et al 1996;Lin and Chen 1997;Volff et al 1997;Qin and Cohen 1998;Volff and Altenbuchner 2000). Southern blot analysis of chromosomal DNA isolated from two individual survivors (BKKO5 and BKKO6) indicated that these survivors had, in fact, undergone the telomere loss (Fig.…”
Section: Tpg Protein Is Required For the Propagation Of Linear Plasmimentioning
confidence: 99%
See 1 more Smart Citation
“…Since the three SCP1 replication loci could independently determine propagation in both circular and linear modes in Streptomyces, we tried to use a previous strategy for circularization of Streptomyces linear chromosomes (Lin & Chen, 1997) to artificially circularize SCP1 at 621-284 635 bp, which contained the three replication loci. Plasmid pSY29 was integrated by conjugal transfer into SCP1 of S. coelicolor J841 and then three clones with a phenotype of Thio S /Apr R were obtained after screening 25 colonies, indicating occurrence of a double-crossover event.…”
Section: Three Replication Loci Determine Propagation Independently Imentioning
confidence: 99%